Informação, participação e cobrança pelo uso da água: um relato do processo no comitê para integração da bacia do rio Paraíba do Sul - Abreu, Claudia Santiago de (2006)
This essay reports the use of information in the decisive process that took place in the basin of Paraíba do Sul River when charging for the use of untreated water was implemented, determined by National Policy of Hydro Resources, in the year of 1997. This hydrographic basin is of great importance to the national scenery of Brazil (since it is located between the two largest cities of the country). It was choosen as the focus of this study because it was a pioneer experience in implementing a Management System of Hydro Resources in rivers of Union domain, having as background the complexity of Brazilian federalism and the lack of tradition in participative processes of making decisions in this field. This study shows how the fact of charging for the use of water was an agglutinative factor for all the actors in the basin, how the accumulative social capital was fundamental for the negotiation process, and finally how the use of technical information, contrary to what was expected, led to significant advances in methodology and criteria proposed for implementation of this important instrument of water management.